Inulinase from Kluyveromyces marxianus: culture medium composition and enzyme extraction - A. PESSOA JR (Brazilian Journal of Chemical Engineering, 1999)
K. marxianus DSM 70106 was cultivated for inulinase production in a medium containing 2.0 g/L of yeast extract, 5.0 g/L of peptone and salts. The addition of corn steep liquor did not increase enzyme production. Inulin, as the main carbon source, afforded higher inulinase production than glucose, fructose, sucrose, lactose, maltose and starch. Glucose, fructose and sucrose reduced enzyme production by 46, 58 and 71%, respectively. By using the best culture medium enzyme activity remained stable for 22 months at 4oC; while at -18oC it decreased by 10%. Maximal activity was found in the pH range of 3.5 to 5.0 and at temperatures from 50 to 60oC. Flocculation was used for cell separation. Shifting the pH was more efficient than using polyelectrolytes, CaCl2, bentonite and Fe2O3. Recovery of inulinase by AOT(sodium di-2-ethylhexyl sulfosuccinate)-reversed micelles yielded up to ~20%.